Tuning the phase composition in polymorphic Nb2O5 nanoplates for rapid and stable lithium ion storage. (10th December 2021) - Zhang, Wanxing; Shen, Peixing; Qian, Lizhi; Mao, Pengcheng; Ahmad, Mashkoor; Chu, Hongtao; Zheng, Runguo; Wang, Zhiyuan; Bai, Lu; Sun, Hongyu; Yu, Yanlong; Liu, Yanguo
Highlights: The phase composition is tuned in polymorphic Nb2O5 nanoplates. The optimized sample shows improved lithium storage properties. The enhanced performance is attributed to the nanoscale phase structure and interface. Abstract: By using the intrinsic polymorphism nature of Nb2 O5 material, we employ three typical Nb2 O5 phases (orthorhombic (T), tetragonal (M) and monoclinic (H) phases) in a single material, and optimize the phase composition to form nanodomains, which are achieved by carefully adjusting the calcination parameters. The resulting sponge-like Nb2 O5 nanoplate anodes exhibit attractive rate performance and cycle stability. Specifically, the optimized electrode shows a reversible capacity of 321 mAh g −1 at 1 C (1 C = 200 mA g −1 ) after 200 cycles. At a high current density of 10 C, the electrode delivers a reversible capacity of 152 mAh g −1 . Long term durability tests show that the electrode performs an excellent cycling performance at a current density of 5 C over 1000 cycles with a capacity loss of 0.06 mAh g −1 per cycle. The excellent lithium storage properties are due to the unique multiple phases and nanoscale interface inside the electrode, which facilitate the storing of more ions and the rapid ion transportation during the charging/discharging process. The proposed electrode design strategy provides an alternative route to develop advanced electrodes for energy storage. Graphical abstract: Tuning the phase composition in polymorphic Nb2 O5 nanoplates anode leads to improved electrochemical lithium storage performance. Image, graphical abstract